Before she was Helen - Cooney, Caroline B. (Poisoned Pen Press, 2020)
"Clementine Lakefield leads a simple life in her retirement community in Sun City, South Carolina. But while she plays cards, substitute teaches, and has learned to text with her niece and nephew, Clemmie is not who she says she is. Behind her carefree facade, she is hiding a lifetime of secrets. When Clemmie's curmudgeonly neighbor goes missing, Clemmie suddenly finds herself at the center of a dangerous conspiracy..."--